2013
DOI: 10.1021/ol400926p
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalyzed Asymmetric Synthesis of Morphans

Abstract: A general effective organocatalyzed synthesis of enantioenriched morphans with up to 92% ee was developed. The morphan scaffold was constructed in a one-pot tandem asymmetric organocatalyzed Michael addition followed by a domino Robinson annulation/aza-Michael intramolecular reaction sequence from easily available starting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…As shown in Scheme 27, using 1,3-diketo esters 101 and enals 102 as the substrates,m orphans 103 were obtained in good yields and high ee values by using (R)-59 as the catalyst. [61] These authors later successfully synthesized lycoposerramine Z( 106), using as imilar reaction strategyw ith as lightly modified substrate 104 (Scheme 27). [62] Derivatives of dodecahydrobenz[a]indolo[3,2-h]quinolizine [63] (109,i nside yohimbane), pro-aza-yohimbane (111), and 7-azaindole-octahydroisoquinolin-3-one [64] (112,i nside-aza-yohimbane) were synthesized in excellent stereoselectivities by Hong, Chou, and co-workers via ad ouble Michaelr eaction catalyzed by chiral secondary amine (S)-45 and as uccessive domino Pictet-Spengler/lactamf ormation reaction mediated by the Brønsted acid TFA.…”
Section: Scheme23mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Scheme 27, using 1,3-diketo esters 101 and enals 102 as the substrates,m orphans 103 were obtained in good yields and high ee values by using (R)-59 as the catalyst. [61] These authors later successfully synthesized lycoposerramine Z( 106), using as imilar reaction strategyw ith as lightly modified substrate 104 (Scheme 27). [62] Derivatives of dodecahydrobenz[a]indolo[3,2-h]quinolizine [63] (109,i nside yohimbane), pro-aza-yohimbane (111), and 7-azaindole-octahydroisoquinolin-3-one [64] (112,i nside-aza-yohimbane) were synthesized in excellent stereoselectivities by Hong, Chou, and co-workers via ad ouble Michaelr eaction catalyzed by chiral secondary amine (S)-45 and as uccessive domino Pictet-Spengler/lactamf ormation reaction mediated by the Brønsted acid TFA.…”
Section: Scheme23mentioning
confidence: 99%
“…[61] These authors later successfully synthesized lycoposerramine Z( 106), using as imilar reaction strategyw ith as lightly modified substrate 104 (Scheme 27). [62] Derivatives of dodecahydrobenz[a]indolo[3,2-h]quinolizine [63] (109,i nside yohimbane), pro-aza-yohimbane (111), and 7-azaindole-octahydroisoquinolin-3one [64] (112,i nside-aza-yohimbane) were synthesized in excellent stereoselectivities by Hong, Chou, and co-workers via ad ouble Michaelr eaction catalyzed by chiral secondary amine (S)-45 and as uccessive domino Pictet-Spengler/lactamf ormation reaction mediated by the Brønsted acid TFA. Compounds 109 and 112 both contain five contiguous stereogenic centers.A ss hown in Scheme 28, ethyl trans-6-nitrohex-2enoate (107)a nd the a,b-unsaturated aldehydes 42 first underwent ad ouble Michael reaction to form the cyclohexanecarbaldehyde intermediates 108.T reatment of 108 with substrates 110 or 113 in the presence of TFAi naone-pot manner providedt he desired products via ad omino Pictet-Spengler/lactam formation reaction.…”
Section: 211synthesis Of Aza-heterocyclesmentioning
confidence: 99%
“…Indeed, this proved to be the case and allowed us to achieve the first efficient synthetic entry to the morphan nucleus using organocatalysis from simple acyclic precursors. 5 Here, we expand the scope of this strategy to include the octahydroindole unit, 6 another privileged scaffold found in an extensive and diverse range of compounds ( Figure 2). These include natural products such as aeruginosin 298-A, 7 lycorine, 8 daphniyunnine D, 9 neotuberostemonine, 10 pharmaceutical products such as perindopril, 11 and a number of proline analogue organocatalysts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…develop an ew catalytic asymmetric method to access the morphan motif with high efficiencya nd selectivity.R etrosynthetic analysis revealed that ad irect approach could exploit ad esymmetrization [3] of prochiral ketone I by an intramolecular Michael addition reaction to an a,b-unsaturated ester under enamine catalysis. [4] Although aldol variants of this type are known, [5] such acatalytic asymmetric Michael reaction has not been reported to date,despite its potential to directly provide morphan skeleton II,w hich possesses three stereocenters and at wo carbon appendage useful for subsequent synthetic manipulation (Scheme 1). [6] Accordingly, we viewed this proposed desymmetrization reaction as agood opportunity to unveil new reactivity in organocatalysis whilst accessing key bicyclic building blocks that are useful for the synthesis of morphan-like natural product libraries.…”
mentioning
confidence: 99%
“…Va riations to the prochiral scaffold were next investigated. Thespirocyclic pyrrolidine-containing a,b-unsaturated esters 2e-2h were excellent substrates,although it was necessary to increase the benzoic acid co-catalyst loading to 2.5 mol %t o maintain good reaction rates (entries [5][6][7][8]. Pleasingly an onspirocyclic substrate possessing N-ethyl and 4-methyl substituents underwent cyclization with equally high diastereoand enantiocontrol (96 % ee)b ut at am arginally diminished reaction rate (entry 9).…”
mentioning
confidence: 99%